Design an Off- Grid Solar System to Identify the Accuracy of the Data Obtained by Calculation and Actual Situation - Shanker, Sharvin; TS.Mohd Fadly Bin Abd Razak, (Progress in Engineering Application and Technology, 2023)
This Off-grid solar power systems are becoming more and more common as independent and sustainable sources of electricity, especially in outlying locations without connection to the traditional power grid. Several factors, including solar panel capacity, battery storage capacity, charge controller efficiency, and inverter performance, will be taken into account to evaluate the correctness of the generated data. The steps in the design process involve determining out the target systems energy needs, estimating the solar panel capacity needed to produce the desired amount of electricity, choosing a suitable battery storage system to hold any extra energy, and selecting an effective charge controller and inverter. To assess the designs accuracy, the computed values will be contrasted with the actual system performance. The evaluation procedure will take into consideration actual environmental factors such as weather patterns, solar radiation levels, temperature changes, and system losses. To measure the actual energy generation, battery state of charge, and overall system performance over a predetermined timeframe, monitoring equipment will be installed. To evaluate the accuracy of the design, this data will be compared with the projected values discovered by calculations. The results of this study will give important information on the precision of the data collected through calculations for off-grid solar system design. Future designs will benefit from its optimization and refinement, resulting in off-grid solar systems that are more dependable and effective